2015
DOI: 10.1073/pnas.1507622112
|View full text |Cite
|
Sign up to set email alerts
|

Stonefish toxin defines an ancient branch of the perforin-like superfamily

Abstract: The lethal factor in stonefish venom is stonustoxin (SNTX), a heterodimeric cytolytic protein that induces cardiovascular collapse in humans and native predators. Here, using X-ray crystallography, we make the unexpected finding that SNTX is a pore-forming member of an ancient branch of the Membrane Attack ComplexPerforin/Cholesterol-Dependent Cytolysin (MACPF/CDC) superfamily. SNTX comprises two homologous subunits (α and β), each of which comprises an N-terminal pore-forming MACPF/CDC domain, a central focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 64 publications
2
59
0
2
Order By: Relevance
“…Among these toxin genes, we also found several genes that have high sequence similarities to the stonefish toxin, stonustoxin. Stonustoxin is a pore-forming protein of the membrane attack complex-perforin/cholesterol-dependent cytolysin superfamily, which is widely distributed among eukaryotes 52 . Wide distribution of this gene in non-toxic taxa suggests that it may play a broader role than envenomation.…”
Section: Lineage-specific Expansion Of Innate Immune Genesmentioning
confidence: 99%
“…Among these toxin genes, we also found several genes that have high sequence similarities to the stonefish toxin, stonustoxin. Stonustoxin is a pore-forming protein of the membrane attack complex-perforin/cholesterol-dependent cytolysin superfamily, which is widely distributed among eukaryotes 52 . Wide distribution of this gene in non-toxic taxa suggests that it may play a broader role than envenomation.…”
Section: Lineage-specific Expansion Of Innate Immune Genesmentioning
confidence: 99%
“…In our work, SLS, SAXS and NS-EM consistently indicate that native PV2 is a dimer of heterodimers. As far as we know, there is only a single report of another MACPF secreted as a structurally-stable water-soluble dimer (Ellisdon et al, 2015) and not as monomers as the vast majority of MACPF. Interestingly, this dimeric MACPF is also a cytotoxin, the fish stonustoxin (SNTX).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this dimeric MACPF is also a cytotoxin, the fish stonustoxin (SNTX). However, unlike PV2, SNTX do not have a lectin subunit, or even a carbohydrate-binding domain (Ellisdon et al, 2015). The reason for this dimeric arrangement is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous reports have shown that the hemolytic effect induced by SNTX was fully prevented by osmotic protectants of adequate size while uncharged molecules of smaller size failed to avert cell lysis [57]. More recently, the pore formation mechanism was directly visualized through transmission electron microscopy of SNTX [58]. …”
Section: Bioactive Proteins Isolated From Spvmentioning
confidence: 99%